(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2018)
The problem of finding proper set-theoretic foundations for category theory has challenged mathematician since the very beginning. In this paper we give an analysis of some of the standard approaches that have been proposed in the past 70 years. By means of the central notions of class and universe we suggest a possible conceptual recasting of these proposals. We focus on the intended semantics for the (problematic) notion of large category in each proposed foundation. Following Feferman (2006) we give a comparison and evaluation of their expressive power.